Enhanced Freeze‐Thaw Cycle Altered the Simulations of Groundwater Dynamics in a Heavily Irrigated Basin in the Temperate Region of China - Baogui Li; Lili Tan; Xueliang Zhang; Junyu Qi; Gary W. Marek; Puyu Feng; De Li Liu; Xi Luo; Raghavan Srinivasan; Yong Chen (Water Resources Research)
Abstract With intensified global warming, accurate quantification of hydrological processes in seasonally frozen regions, particularly with irrigated overwinter crops, is necessary to develop management strategies that promote groundwater conservation. By incorporating a physically based freeze‐thaw cycle module into the Soil and Water Assessment Tool (SWAT‐FT) model, variations of surface hydrology and groundwater dynamics were systematically assessed in North China Plain under three Shared Socioeconomic Pathways during 2041–2070 and 2071–2100 periods between the conventional and improved SWAT models. Compared to the conventional SWAT model, the SWAT‐FT model predicted an increase in soil water content, decrease in irrigation, and an increase in percolation during the growing season of winter wheat. These discrepancies resulted in a 5% higher decline rates of shallow groundwater levels simulated by the SWAT model compared to the SWAT‐FT. Additionally, the SWAT‐FT model projected that the average decline rates of shallow groundwater levels were approximately 0.90 ± 0.16 m yr−1 (SSP1‐2.6), 0.60 ± 0.46 m yr−1 (SSP2‐4.5), and −0.17 ± 0.53 m yr−1 (SSP5‐8.5), respectively, during 2071–2100 compared to the historical period. The SWAT‐FT simulations indicated that the decline rates in shallow groundwater levels were projected to either decrease slowly or potentially increase by the end of the 21st century under the SSP5‐8.5 scenario, potentially achieving equilibrium between shallow groundwater extraction and replenishment. Our study emphasized the importance of considering the freeze‐thaw processes to evaluate groundwater variations more accurately in response to climate change effects in temperate regions with an overwinter crop.